2001
DOI: 10.1029/2000ja003018
|View full text |Cite
|
Sign up to set email alerts
|

Observations of relativistic electron microbursts in association with VLF chorus

Abstract: Abstract.The Solar, Anomalous and Magnetospheric Particle Explorer (SAMPEX) satellite frequently observes relativistic (> 1 MeV) electron precipitation in the radiation belts at oe shells of 4-6 with bursty temporal structure lasting < 1 s. This phenomenon can occur at all local times but is most often seen between 0200 and 1000 magnetic local time. VLF chorus is also observed to occur preferentially at these same local times. Using electron observations from the SAMPEX satellite Heavy Ion Large Telescope and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
315
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(331 citation statements)
references
References 39 publications
16
315
0
Order By: Relevance
“…In addition, it should be noted that the parallel e-folding energy and fluxes are smaller than the perpendicular ones even during the storm. While Lorentzen et al (2001) and O'Brien et al (2004) calculated microburst loss rate by assuming isotropic pitch angle distributions, our observations indicate energetic electron loss might be smaller than their estimation.…”
Section: Resonance Condition For Wave Particle Interaction 14mentioning
confidence: 42%
See 1 more Smart Citation
“…In addition, it should be noted that the parallel e-folding energy and fluxes are smaller than the perpendicular ones even during the storm. While Lorentzen et al (2001) and O'Brien et al (2004) calculated microburst loss rate by assuming isotropic pitch angle distributions, our observations indicate energetic electron loss might be smaller than their estimation.…”
Section: Resonance Condition For Wave Particle Interaction 14mentioning
confidence: 42%
“…Some researchers have calculated electron precipitation rates of relativistic microbursts and showed wave particle interaction is a dominant electron loss process of radiation belt-relativistic electrons (Lorentzen et al, 2001;O'Brien et al, 2004;Thorne et al, 2005). They estimated the electron loss rate using SAMPEX data assuming downward isotropic pitch angle distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The pitch-angle scattering of the radiation belt energetic electrons by chorus can lead to significant precipitation into the atmosphere [Lorentzen et al, 2001;Meredith et al, 2001;Summers, 2005]. Tsurutani and Smith [1974] and Anderson and Maeda [1977] found that the onset of the chorus emissions coincided with the injection of substorm electrons with energies of ∼10-100 keV.…”
Section: Introductionmentioning
confidence: 99%
“…The bottom panel shows a line plot of the estimated minimum daily plasmapause position [O'Brien and Moldwin, 2003]. Superimposed on the line plot are colored bars indicating where electron precipitation microbursts [Lorentzen et al, 2001a and2001b;] were observed at L < 4 (red bars) and L > 4 (blue bars).…”
Section: Observationsmentioning
confidence: 99%